Low-density ceramic pouring sealant composition as well as preparation method and application thereof
By developing a low -density can be perforated and sealing the composition, the problem of high existing heat insulation materials, complex process and failure at high temperatures have been solved, and the low density, low heat conduction and high temperature can be ceramic insulation effects of power batteries are achieved. , Significantly improved the safety performance of the battery.
Patent Information
- Application Number
- CN202411529182.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
AI Technical Summary
The thermal insulation materials in existing power batteries have problems such as high cost, complex process, poor durability, temperature difference, flame retardant and failure at high temperatures, making it difficult to effectively improve the safety performance of power batteries.
Develop a low -density ceramic and sealing composition, and use the mixed preparation of components and B components to use base materials, basic polymers, low -density fillers, crosslinters and inhibitors to form a low low. Density, low heat -conducting and high -temperature insulation materials.
While achieving low density and low thermal conductivity, it has good flame retardant performance and high-temperature ceramic performance. It can quickly become ceramic body at a high temperature of 1000-1300 ° C, further transmission of heat blocking, and improve the power battery. Safety performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic silicon potting glue molding processing and production, and particularly relates to a low-density ceramic potting glue composition and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy electric vehicles, the safety issues of power batteries are becoming increasingly severe. How to improve the safety performance of power batteries is particularly important. Power batteries, especially ternary lithium power batteries, are more prone to thermal runaway when squeezed, vibrated, or even short-circuited during charging and discharging. After a single battery cell has thermal runaway, the instantaneous temperature can reach 1300°C or above, causing the surrounding batteries to overheat, causing all batteries to thermally runaway together, the entire battery pack to catch fire, and even explode. At present, different batteries in the industry use different insulation materials to block heat transfer between batteries. Among them, square batteries and soft-pack battery packs usually use PET-sealed aerogel insulation pads, which are placed between two batteries to block heat transfer; cylindrical battery packs usually choose to use low thermal conductivity polyurethane potting glue to block heat transfer. Square battery packs and soft-pack battery packs use PET-sealed aerogel insulation pads to block heat. Due to the low thermal conductivity of aerogel, it can indeed achieve a certain thermal insulation effect. However, the preparation process of the plastic-sealed aerogel insulation pad is relatively complicated and costly. At the same time, in order to be bonded between each battery cell, the insulation pad needs to be backed by double-sided tape. Not only is the material cost high, but the bonding process cost is also high. At the same time, PET plastic film and double-sided tape also have problems such as poor durability, temperature difference resistance, and poor flame retardancy. In addition, pure PET-sealed aerogel does not have good compression rebound performance. During the charging and discharging process of the battery, there will be changes in expansion stress, and buffer materials are needed to absorb the stress. Aerogel insulation pads usually need to be surrounded by silicone rubber circular frames with good rebound performance to provide buffering performance, which makes the molding process more complicated and the cost higher. Cylindrical battery packs usually use low thermal conductivity polyurethane potting glue with a thermal conductivity of about 0.3w / mk, which is higher than the thermal conductivity of aerogel insulation pads and has strong heat transfer capacity; but it also has the characteristics of poor flame retardancy, temperature difference resistance, and poor rebound. Especially at high temperatures of 1300°C, the polyurethane potting glue will almost quickly fail. Summary of the invention
[0003] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a low-density ceramic potting compound.
[0004] Another object of the present invention is to provide a method for preparing the low-density ceramic potting compound.
[0005] Another object of the present invention is to provide an application of the low-density ceramic potting compound.
[0006] The purpose of the present invention is achieved through the following technical solutions: A low-density ceramic potting compound composition comprises component A and component B; wherein: Component A comprises the following ingredients by mass: 100 parts of base material, 5-50 parts of base polymer, 1-30 parts of low-density filler, 0-2 parts of colorant, 0.01-1 parts of catalyst; preferably comprises the following ingredients by mass: 100 parts of base material, 30-50 parts of base polymer, 1-20 parts of low-density filler, 0-0.5 parts of colorant, 0.01-0.5 parts of catalyst; more preferably comprises the following ingredients by mass: 100 parts of base material, 32-47 parts of base polymer, 2-18 parts of low-density filler, 0.1-0.5 parts of colorant, 0.3-0.5 parts of catalyst; Component B comprises the following ingredients in parts by mass: 100 parts of base material, 5-50 parts of base polymer, 1-30 parts of low-density filler, 1-15 parts of cross-linking agent, and 0.01-0.1 parts of inhibitor; preferably comprises the following ingredients in parts by mass: 100 parts of base material, 20-40 parts of base polymer, 1-20 parts of low-density filler, 5-15 parts of cross-linking agent, and 0.01-0.05 parts of inhibitor; more preferably comprises the following ingredients in parts by mass: 100 parts of base material, 20-32 parts of base polymer, 2-18 parts of low-density filler, 6-12 parts of cross-linking agent, and 0.01-0.02 parts of inhibitor.
[0007] The base material is prepared by the following steps: heating a base polymer, a flame retardant filler and a ceramic filler under stirring to 105±5°C, opening a vacuum, maintaining a negative pressure of 0.1MPa, and reacting under stirring to obtain the base material; wherein the composition of each component is as follows by mass: 30-150 parts of base polymer, 50-200 parts of flame retardant filler and 30-150 parts of ceramic filler; preferably as follows: 100-150 parts of base polymer, 50-150 parts of flame retardant filler and 50-150 parts of ceramic filler.
[0008] The insulation reaction time is preferably 90 to 150 minutes, and more preferably 120 minutes.
[0009] The base polymer is vinyl polysiloxane; preferably at least one of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil and side-chain vinyl silicone oil.
[0010] The viscosity of the vinyl polysiloxane is preferably 50 cs-20000 cs; more preferably 50 cs-1000 cs; most preferably 50 cs-500 cs.
[0011] The flame retardant filler includes a halogen-containing flame retardant filler and a halogen-free flame retardant filler.
[0012] The halogen-containing flame retardant filler is preferably a brominated flame retardant; more preferably a brominated environmentally friendly flame retardant, including at least one of hexabromodiphenylethane (also known as hexabromocyclododecane), octabromodiphenylethane and decabromodiphenylethane.
[0013] The halogen-free flame retardant filler is preferably at least one of aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate, expanded graphite powder and montmorillonite powder. When the low-density filler is an organic substance, such as a hollow acrylic elastomer, the halogen-free flame retardant filler is preferably a composite of aluminum hydroxide and sodium polyphosphate; more preferably, aluminum hydroxide and sodium polyphosphate are used in a mass ratio of 2:1.
[0014] The particle size of the flame retardant filler is preferably 1-100 μm, more preferably 1-15 μm, and most preferably 1-10 μm.
[0015] The ceramic filler is an inorganic filler with fireproof performance; preferably at least one of wollastonite powder, calcium silicate powder, talcum powder and glass powder.
[0016] The particle size of the ceramic filler is preferably 1-100 μm, more preferably 3-15 μm, and most preferably 5-13 μm.
[0017] The low-density filler is a hollow filler with a hollow structure; preferably at least one of hollow glass microspheres, hollow acrylic elastomers, hollow silica powders and hollow silica-alumina ceramics.
[0018] The hollow acrylic elastomer is preferably hollow polyacrylate microspheres.
[0019] The density of the low-density filler is preferably 0.02-0.8 g / cm 3 .
[0020] The particle size of the low-density filler is preferably 10-200 μm, more preferably 30-90 μm, and most preferably 30-80 μm.
[0021] The crosslinking agent is hydrogen-containing polysiloxane; preferably at least one of double-end hydrogen-containing silicone oil, single-end hydrogen-containing silicone oil and side-chain hydrogen-containing silicone oil.
[0022] The hydrogen content of the hydrogen-containing silicone oil is preferably 0.05%-0.75%; more preferably 0.05-0.40%.
[0023] The colorant is a colorant commonly used in potting glue, such as a color paste obtained by diluting a colorant with vinyl polysilicone as a diluent; preferably at least one of a black color paste diluted with carbon black, a red color paste diluted with red iron oxide, and a blue color paste diluted with phthalocyanine blue.
[0024] The content of the diluent is preferably 50%-90%.
[0025] The catalyst is a platinum complex; preferably a platinum complex obtained by complexing vinyl polysiloxane with chloroplatinic acid, with a platinum content of 1000-8000ppm; preferably 3000-5000ppm.
[0026] The inhibitor is preferably at least one of ethynyl cyclohexanol, butynol, divinyltetramethyldisiloxane and tetravinyltetramethylcyclotetrasiloxane.
[0027] The method for preparing the low-density ceramic potting compound comprises the following steps: (1) Preparation of component A: The base material, base polymer, low-density filler, colorant and catalyst are uniformly stirred under vacuum conditions to obtain component A; (2) Preparation of component B: The base material, base polymer, low-density filler, crosslinking agent and inhibitor are uniformly stirred under vacuum conditions to obtain component B.
[0028] The vacuum condition is preferably a negative pressure of 0.1 MPa.
[0029] The stirring time is preferably 30-60 min.
[0030] The use of the low-density ceramic potting compound composition in preparing a battery preferably comprises the following steps: mixing component A and component B, which can be used for potting.
[0031] The component A and the component B are preferably mixed in a mass ratio of 1:1.
[0032] Compared with the prior art, the present invention has the following advantages and effects: (1) The preparation method of the low-density ceramic potting compound provided by the present invention is simple and easy to implement, convenient for industrial production, and low in cost.
[0033] (2) The low-density ceramic potting adhesive composition provided by the present invention can replace traditional thermal insulation materials and be used between power battery cells to play a role of thermal insulation and buffering. The assembly process is simple and the fireproof effect is better.
[0034] (3) The low-density ceramic potting compound provided by the present invention not only has the basic properties of potting compounds, including good fluidity, fast curing speed, good flame retardancy and buffering properties, but also has outstanding low density, low thermal conductivity, and ceramic properties at high temperatures, and can meet the requirements of compressive stress, flame retardancy, heat insulation, and fire prevention between battery cells.
[0035] Compared with the aerogel insulation pad used in the prior art, the present invention has low preparation cost, simple process, low construction cost and easy operation; compared with the low-density potting glue in the prior art, while maintaining good flame retardancy, it increases the ceramic function at high temperature. At a temperature of 1000-1300°C, it can quickly become a ceramic body to further block the transfer of heat. At the same time, after becoming ceramic, it has good bending resistance and can block the impact of heat; while the traditional low-density potting glue, under the high temperature as mentioned above, although it has flame retardant properties, it is not non-flammable and is completely burned in an instant. It cannot block the impact of heat and cannot ensure the safety performance of the battery. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. The parts in the examples are parts by mass.
[0037] Example 1 (1) Put 100 parts of vinyl-terminated silicone oil (also known as vinyl-terminated polydimethylsiloxane, which is double-end vinyl-terminated silicone oil, the same below) with a viscosity of 100 cs, 150 parts of aluminum hydroxide with a median particle size of 10 μm, 40 parts of calcium silicate with a median particle size of 5 μm, and 10 parts of glass powder with a median particle size of 10 μm into a kneader, turn on heating and stirring, and when the material temperature is heated to 105°C, turn on vacuum, maintain a negative pressure of 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C and discharge it, and cool it to room temperature to obtain base material 1.
[0038] (2) Take 100 parts of the prepared base material 1, 32 parts of 100 cs vinyl-terminated silicone oil, 18 parts of 65 μm hollow glass microspheres, 0.1 parts of gray colorant, and 0.3 parts of 5000 ppm platinum complex (platinum catalyst), put them into a power mixer and stir, turn on the vacuum, and stir for 40 minutes at a negative pressure of 0.1 MPa until the rubber material is evenly stirred, and obtain component A.
[0039] (3) Take 100 parts of the prepared base material 1, 20 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 18 parts of hollow glass microspheres with a particle size of 65 μm, 12 parts of side chain hydrogenated silicone oil with a Si-H mass content of 0.18% (also known as side chain hydrogenated polydimethylsiloxane, the same below), and 0.01 parts of acetylene alcohol inhibitor (10% concentration of ethynyl cyclohexanol dilution), put them into a power mixer and stir, turn on the vacuum, stir at a negative pressure of 0.1 MPa for 40 minutes, until the rubber material is stirred evenly, and obtain component B.
[0040] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare a sheet sample 1 to test the properties.
[0041] Example 2 (1) Put 100 parts of vinyl-terminated silicone oil with a viscosity of 500 cs, 100 parts of aluminum hydroxide with a median particle size of 10 μm, 50 parts of polyphosphoric acid amine with a median particle size of 5 μm, 30 parts of wollastonite with a median particle size of 10 μm, and 20 parts of glass powder with a median particle size of 10 μm into a kneader, turn on heating and stirring, and when the material temperature is heated to 105°C, turn on vacuum, maintain a negative pressure of 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C, discharge the material, and cool it to room temperature to obtain base material 1.
[0042] (2) Take 100 parts of the prepared base material 1, 47 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 2 parts of hollow polyacrylate microspheres with a median particle size of 75 μm, 0.5 parts of red colorant, and 0.5 parts of 3000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber material is evenly stirred, and obtain component A.
[0043] (3) Take 100 parts of the prepared base material 1, 32 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 2 parts of hollow polyacrylate microspheres with a median particle size of 75 μm, 6 parts of side chain hydrogen-containing silicone oil with a Si-H mass content of 0.36%, and 0.01 part of acetylene alcohol inhibitor (20% butynol dilution solution), put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber is evenly stirred, and obtain component B.
[0044] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare a second sheet sample to be tested for performance.
[0045] Example 3 (1) Put 80 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 20 parts of single-terminated silicone oil with a viscosity of 1000 cs, 50 parts of magnesium hydroxide with a median particle size of 10 μm, 50 parts of wollastonite powder with a median particle size of 8 μm, 70 parts of calcium silicate with a median particle size of 13 μm, and 30 parts of glass powder with a median particle size of 9 μm into a kneader, turn on heating and stirring, and when the material temperature is heated to 105°C, turn on vacuum, maintain a negative pressure of 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C, discharge the material, and cool it to room temperature to obtain base material 1.
[0046] (2) Take 100 parts of the prepared base material 1, 35 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 15 parts of hollow silica microspheres with a median particle size of 40 μm, 0.1 parts of blue colorant, and 0.3 parts of 5000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber material is evenly stirred, and obtain component A.
[0047] (3) Take 100 parts of the prepared base material 1, 25 parts of terminal vinyl silicone oil with a viscosity of 100 cs, 15 parts of hollow silica microspheres with a median particle size of 30 μm, 3 parts of side chain hydrogen-containing silicone oil with an Si-H mass content of 0.36%, 7 parts of terminal hydrogen-containing silicone oil with an Si-H mass content of 0.05%, and 0.01 part of acetylene alcohol inhibitor (a mixture of ethynyl cyclohexanol and butynol with a concentration of 12% and a mass ratio of ethynyl cyclohexanol to butynol of 1:1), put them into a power mixer and stir, turn on the vacuum, stir at a negative pressure of 0.1 MPa for 40 minutes, until the rubber material is evenly stirred, and obtain component B.
[0048] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare a sheet sample 3 to be tested for performance.
[0049] Example 4 (1) Put 80 parts of end-vinyl silicone oil with a viscosity of 50 cs, 20 parts of single-end vinyl silicone oil with a viscosity of 400 cs, 70 parts of magnesium hydroxide with a median particle size of 10 μm, 20 parts of expanded graphite powder with a median particle size of 3 μm, 10 parts of montmorillonite powder with a median particle size of 1 μm, 50 parts of calcium silicate with a median particle size of 8 μm, and 50 parts of talc powder with a median particle size of 10 μm into a kneader, turn on heating and stirring, and when the material temperature is heated to 105°C, turn on vacuum, maintain negative pressure of 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C and discharge it, and cool it to room temperature to obtain base material 1.
[0050] (2) Take 100 parts of the prepared base material 1, 35 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 10 parts of hollow glass microspheres with a median particle size of 50 μm, 5 parts of hollow silica-alumina ceramics (3M) with a median particle size of 60 μm, 0.1 parts of blue colorant, and 0.3 parts of 5000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, stir for 40 minutes at a negative pressure of 0.1 MPa, until the rubber material is stirred evenly, and obtain component A.
[0051] (3) Take 100 parts of the prepared base material 1, 27 parts of terminal vinyl silicone oil with a viscosity of 100 cs, 10 parts of hollow glass microspheres with a median particle size of 50 μm, 5 parts of hollow silica-alumina ceramics with a median particle size of 60 μm, 4 parts of terminal hydrogen-containing silicone oil with an Si-H mass content of 0.1%, 4 parts of side chain hydrogen-containing silicone oil with an Si-H mass content of 0.36%, and 0.01 part of acetylene alcohol inhibitor (a mixture of ethynyl cyclohexanol and butynol with a concentration of 20%, in which ethynyl cyclohexanol and butynol are mixed in a ratio of 1:1 by mass), put them into a power mixer and stir, turn on the vacuum, stir at a negative pressure of 0.1 MPa for 40 minutes, until the rubber material is stirred evenly, and discharge the material to obtain component B.
[0052] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare a sheet sample 4 to be tested for performance.
[0053] Example 5 (1) Put 150 parts of vinyl-terminated silicone oil with a viscosity of 500 cs, 100 parts of decabromodiphenylethane, 30 parts of wollastonite with a median particle size of 10 μm, and 20 parts of glass powder with a median particle size of 10 μm into a kneader, turn on heating and stirring, and when the material temperature reaches 105°C, turn on vacuum, maintain the negative pressure at 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C, discharge the material, and cool it to room temperature to obtain base material 1.
[0054] (2) Take 100 parts of the prepared base material 1, 47 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 2 parts of hollow polyacrylate microspheres with a median particle size of 75 μm, 0.5 parts of red colorant, and 0.5 parts of 3000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber material is evenly stirred, and obtain component A.
[0055] (3) Take 100 parts of the prepared base material 1, 32 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 2 parts of hollow polyacrylate microspheres with a median particle size of 75 μm, 6 parts of side chain hydrogen-containing silicone oil with a Si-H mass content of 0.36%, and 0.01 part of acetylene alcohol inhibitor (20% butynol dilution solution), put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber is evenly stirred, and obtain component B.
[0056] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly at a mass ratio of 1:1 to obtain a potting compound, and prepare sheet sample 5 to be tested for performance.
[0057] Comparative Example 1 The only difference from Example 2 is that the flame retardant does not use polyphosphate amine, but only uses aluminum hydroxide, as follows: (1) Put 100 parts of vinyl-terminated silicone oil with a viscosity of 500 cs, 150 parts of aluminum hydroxide with a median particle size of 10 μm, 30 parts of wollastonite with a median particle size of 10 μm, and 20 parts of glass powder with a median particle size of 10 μm into a kneader, turn on heating and stirring, and when the material temperature reaches 105°C, turn on vacuum, maintain the negative pressure at 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C, discharge the material, and cool it to room temperature to obtain base material 1.
[0058] (2) Take 100 parts of the prepared base material 1, 47 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 2 parts of hollow polyacrylate microspheres with a median particle size of 75 μm, 0.5 parts of red colorant, and 0.5 parts of 3000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber material is evenly stirred, and obtain component A.
[0059] (3) Take 100 parts of the prepared base material 1, 32 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 2 parts of hollow polyacrylate microspheres with a median particle size of 75 μm, 6 parts of side chain hydrogen-containing silicone oil with a Si-H mass content of 0.36%, and 0.01 part of acetylene alcohol inhibitor (20% butynol dilution solution), put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber is evenly stirred, and obtain component B.
[0060] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare sheet sample 6 to be tested for performance.
[0061] Comparative Example 2 The only difference from Example 3 is that calcium silicate powder is used to replace the glass powder in Example 3, as follows: (1) 80 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 20 parts of single-terminated silicone oil with a viscosity of 1000 cs, 50 parts of magnesium hydroxide with a median particle size of 10 μm, 50 parts of wollastonite powder with a median particle size of 8 μm, and 100 parts of calcium silicate with a median particle size of 13 μm are put into a kneader, and heating and stirring are started. When the material temperature is heated to 105°C, vacuum is turned on, and the negative pressure is maintained at 0.1 MPa. Heat and stir for 2 hours, then cool the material to about 60°C, discharge the material, and cool it to room temperature to obtain base material 1.
[0062] (2) Take 100 parts of the prepared base material 1, 35 parts of vinyl-terminated silicone oil with a viscosity of 100 cs, 15 parts of hollow silica microspheres with a median particle size of 40 μm, 0.1 parts of blue colorant, and 0.3 parts of 5000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber material is evenly stirred, and obtain component A.
[0063] (3) Take 100 parts of the prepared base material 1, 25 parts of terminal vinyl silicone oil with a viscosity of 100 cs, 15 parts of hollow silica microspheres with a median particle size of 30 μm, 3 parts of side chain hydrogen-containing silicone oil with an Si-H mass content of 0.36%, 7 parts of terminal hydrogen-containing silicone oil with an Si-H mass content of 0.05%, and 0.01 part of acetylene alcohol inhibitor (a mixture of ethynyl cyclohexanol and butynol with a concentration of 12% and a mass ratio of ethynyl cyclohexanol to butynol of 1:1), put them into a power mixer and stir, turn on the vacuum, stir at a negative pressure of 0.1 MPa for 40 minutes, until the rubber material is evenly stirred, and obtain component B.
[0064] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare sheet sample 7 to be tested for performance.
[0065] Comparative Example 3 The only difference from Example 4 is that hollow silicon-alumina ceramics are used to replace the hollow glass microspheres in Example 4, as follows: (1) Put 80 parts of end-vinyl silicone oil with a viscosity of 50 cs, 20 parts of single-end vinyl silicone oil with a viscosity of 400 cs, 70 parts of magnesium hydroxide with a median particle size of 10 μm, 20 parts of expanded graphene powder with a median particle size of 3 μm, 10 parts of montmorillonite powder with a median particle size of 1 μm, 50 parts of calcium silicate with a median particle size of 8 μm, and 50 parts of talc powder with a median particle size of 10 μm into a kneader, turn on heating and stirring, and when the material temperature is heated to 105°C, turn on vacuum, maintain negative pressure of 0.1 MPa, heat and stir for 2 hours, then cool the material to about 60°C and discharge, and cool to room temperature to obtain base material 1.
[0066] (2) Take 100 parts of the prepared base material 1, 35 parts of end-vinyl silicone oil with a viscosity of 100 cs, 15 parts of hollow silica-alumina ceramics with a median particle size of 60 μm, 0.1 parts of blue colorant, and 0.3 parts of 5000 ppm platinum complex, put them into a power mixer and stir, turn on the vacuum, and stir at a negative pressure of 0.1 MPa for 40 minutes until the rubber material is evenly stirred, and obtain component A.
[0067] (3) Take 100 parts of the prepared base material 1, 27 parts of terminal vinyl silicone oil with a viscosity of 100 cs, 15 parts of hollow silica-alumina ceramics with a median particle size of 60 μm, 4 parts of terminal hydrogen-containing silicone oil with an Si-H content of 0.1%, 4 parts of side chain hydrogen-containing silicone oil with an Si-H content of 0.36%, and 0.01 parts of an acetylene alcohol inhibitor (a mixture of ethynyl cyclohexanol and butynol with a concentration of 20%, wherein ethynyl cyclohexanol and butynol are mixed in a ratio of 1:1 by mass), put them into a power mixer and stir, turn on the vacuum, and stir for 40 minutes at a negative pressure of 0.1 MPa until the rubber material is evenly stirred, and discharge the material to obtain component B.
[0068] (4) Take 100 g of each of the prepared component A and component B and test the viscosity and other properties; mix the components A and B evenly in a mass ratio of 1:1 to obtain a potting compound, and prepare sheet sample 8 to test the properties.
[0069] Effect Example The potting adhesive compositions obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were tested as follows. The results are shown in Table 1.
[0070] Density test refers to "GB / T 6343 Determination of apparent density of cellular plastics and rubber".
[0071] The hardness test refers to GB / T 531.1-2008 Vulcanized rubber or thermoplastic rubber indentation hardness test method Part 1.
[0072] Shore hardness tester method to test Shore hardness.
[0073] The thermal conductivity test refers to "ASTM D5470 Characterization test for testing the thermal conductivity properties of thin thermally conductive solid electrical insulating materials".
[0074] The breakdown voltage test refers to "GB / T 1695-2005 Method for Determination of Power Frequency Breakdown Strength and Withstand Voltage of Vulcanized Rubber".
[0075] The flame retardant rating test refers to the UL94 vertical burning test standard.
[0076] The fireproof and heat-insulating performance test refers to GB / T 10707 Determination of vulcanized rubber. Prepare test pieces with a diameter of 100mm, thickness of 4.5mm and 10mm. Use a butane spray gun, adjust the distance between the flame and the test piece, make the outer flame temperature of the flame 1000℃, continue to spray and burn, and record the time.
[0077] Three-point bending strength test, refer to GB / T 6569-1986 Engineering ceramics bending strength test method.
[0078] As can be seen from the above table, the compositions of the present invention used in Examples 1-5 have suitable initial viscosity and are suitable for potting; after curing, they have low density, low thermal conductivity, good insulation, and good flame retardant properties. They also have excellent heat insulation and fire resistance and burn-through resistance. While meeting the requirements for lightweight power batteries, they also meet the requirements for electrical insulation and heat insulation and fire resistance, further improving the overall safety performance of the battery pack.
[0079] Comparative Example 1 is relative to Example 2, in which aluminum hydroxide is used entirely as the flame retardant, and polyphosphate ammonium is not used, and the obtained sample is not flame retardant. The flame retardant of Example 1 also only uses aluminum hydroxide, but has a flame retardant effect. This may be because hollow polyacrylate microspheres are more flammable than hollow glass microspheres, and its flame retardant needs to be used in combination with aluminum hydroxide and polyphosphate ammonium to have a better effect. As can be seen from Example 5, for hollow polyacrylate microspheres, the halogen-containing flame retardant is used alone, with less usage and better flame retardant effect. The halogen-containing flame retardant has an excellent flame retardant effect on flammable hollow polyacrylate microspheres. Obviously, it also has an excellent flame retardant effect on other hollow materials.
[0080] Comparative Example 2 is relative to Example 3, in which calcium silicate powder is used to replace glass powder. It can be seen that under the condition of meeting the flame retardant requirements, the glass powder has a significant improvement effect on the ceramicization effect and can improve the anti-burn-through performance.
[0081] In Comparative Example 3, relative to Example 4, hollow silicon aluminum oxide ceramics are used to replace hollow glass microspheres. It can be seen that hollow glass microspheres are more conducive to improving the anti-burn-through performance than other hollow materials.
[0082] It can be seen from Examples 1-5 that the composition must contain at least one of glass powder and hollow glass microspheres. Comparative Examples 2 and 3 do not contain glass powder and hollow glass microspheres at all, and the anti-burning performance is reduced. It can be seen that glass powder and / or hollow glass microspheres are essential components in the present invention.
[0083] It can be seen that the present invention innovatively solves the thermal insulation problem, achieves low density and low thermal conductivity, and also satisfies good flame retardancy, ceramicization and burn-through resistance. It can be applied to new energy power batteries to further ensure the safety of power batteries.
[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A low-density ceramic potting compound, characterized in that: It includes component A and component B; wherein: Component A comprises the following ingredients by mass: 100 parts of base material, 5-50 parts of base polymer, 1-30 parts of low-density filler, 0-2 parts of colorant, and 0.01-1 parts of catalyst; Component B comprises the following ingredients by mass: 100 parts of base material, 5-50 parts of base polymer, 1-30 parts of low-density filler, 1-15 parts of cross-linking agent, and 0.01-0.1 parts of inhibitor; The base material is prepared by the following steps: heating a base polymer, a flame retardant filler and a ceramic filler under stirring to 105±5°C, opening a vacuum, maintaining a negative pressure of 0.1 MPa, and reacting under stirring to obtain the base material; wherein the composition of each component is as follows by mass: 30-150 parts of the base polymer, 50-200 parts of the flame retardant filler and 30-150 parts of the ceramic filler; The base polymer is vinyl polysiloxane.
2. The low-density ceramic potting compound composition according to claim 1, characterized in that: The component A comprises the following ingredients by mass: 100 parts of base material, 30-50 parts of base polymer, 1-20 parts of low-density filler, 0-0.5 parts of colorant, and 0.01-0.5 parts of catalyst; The B component comprises the following ingredients in parts by mass: 100 parts of base material, 20-40 parts of base polymer, 1-20 parts of low-density filler, 5-15 parts of cross-linking agent, and 0.01-0.05 parts of inhibitor.
3. The low-density ceramic potting compound composition according to claim 1, characterized in that: The composition of each component in the base material is as follows by weight: 100-150 parts of base polymer, 50-150 parts of flame retardant filler and 50-150 parts of ceramic filler.
4. The low-density ceramic potting compound according to any one of claims 1 to 3, characterized in that: The vinyl polysiloxane is at least one of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil and side-chain vinyl silicone oil; The flame retardant filler includes a halogen-containing flame retardant filler and a halogen-free flame retardant filler; The ceramic filler is at least one of wollastonite powder, calcium silicate powder, talcum powder and glass powder; The low-density filler is at least one of hollow glass microspheres, hollow acrylic elastomers, hollow silica powders and hollow silica-alumina ceramics; The cross-linking agent is hydrogen-containing polysiloxane; The catalyst is a platinum complex; The inhibitor is at least one of ethynyl cyclohexanol, butynol, divinyltetramethyldisiloxane and tetravinyltetramethylcyclotetrasiloxane.
5. The low-density ceramic potting compound composition according to claim 4, characterized in that: The halogen-containing flame retardant filler is a brominated flame retardant; The halogen-free flame retardant filler is at least one of aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate, graphene and montmorillonite powder; The hollow acrylic elastomer is hollow polyacrylate microspheres; The cross-linking agent is at least one of double-terminal hydrogen-containing silicone oil, single-terminal hydrogen-containing silicone oil and side-chain hydrogen-containing silicone oil; The hydrogen content of the cross-linking agent is 0.05%-0.75%; The catalyst is a platinum complex obtained by complexing vinyl polysiloxane with chloroplatinic acid; The platinum content in the catalyst is 1000-8000ppm.
6. The low-density ceramic potting compound composition according to claim 4, characterized in that: The viscosity of the vinyl polysiloxane is 50cs-20000cs; The particle size of the flame retardant filler is 1-100 μm; The particle size of the ceramic filler is 1-100 μm; The particle size of the low-density filler is 10-200 μm.
7. The low-density ceramic potting compound composition according to claim 6, characterized in that: The viscosity of the vinyl polysiloxane is 50cs-1000cs; The particle size of the flame retardant filler is 1-15 μm; The particle size of the ceramic filler is 3-15 μm; The particle size of the low-density filler is 30-90 μm.
8. The method for preparing the low-density ceramic potting composition according to any one of claims 1 to 7, characterized in that The steps include: (1) Preparation of component A: The base material, base polymer, low-density filler, colorant and catalyst are uniformly stirred under vacuum conditions to obtain component A; (2) Preparation of component B: The base material, base polymer, low-density filler, crosslinking agent and inhibitor are uniformly stirred under vacuum conditions to obtain component B.
9. Use of the low-density ceramic potting composition according to any one of claims 1 to 7 in the preparation of batteries.
10. The use according to claim 9, characterized in that The method comprises the following steps: mixing component A and component B, and then the mixture can be used for potting.
Citation Information
Patent Citations
Low-specific-gravity fireproof silicone sealant and preparation method thereof
CN114106767A
Foaming type ceramic heat-insulation fireproof silicone sealant and preparation method thereof
CN114907814A
Flame-impact-resistant ceramic flame-retardant organic silicon pouring sealant as well as preparation method and application thereof
CN118406467A
Cited By
Fireproof heat-insulation organic silicon pouring sealant with fire extinguishing function
CN122483755A